The Concept of Holistic Evaluation in Islamic Education Learning Design: A Synthesis of Tyler, Bloom, and Wiggins Theories - Sheila Rosalia; Hilmi Mizani; Syaiful Bahri; Reza Rachman (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: The Concept of Holistic Evaluation in Islamic Education Learning Design: A Synthesis of Tyler, Bloom, and Wiggins TheoriesObjective: This study aims to develop a holistic evaluation framework for Islamic Education (PAI) instructional design that integrates cognitive, affective, and psychomotor dimensions, grounded in Islamic values. Method: The study employed a qualitative approach using a library research design. Data were collected through document analysis of primary and secondary literature and were examined using content analysis and interpretive synthesis. Results: The synthesis revealed that Tyler’s evaluation model, Bloom’s Taxonomy, and Wiggins’ backward design complement one another in developing authentic assessments that align learning objectives, instructional processes, and evaluation practices. Their integration produces a holistic evaluation model encompassing the dimensions of 'ilm (knowledge), akhlaq (attitude), and amal (practice). Conclusion: This framework enhances the quality of Islamic education instructional design through aligned and authentic evaluation. Contribution: The study offers a conceptual model that can serve as a reference for curriculum developers, educators, and policymakers in designing comprehensive assessment systems for Islamic education.INDONESIAN: Konsep Evaluasi Holistik dalam Desain Pembelajaran Pendidikan Islam: Sintesis Teori Tyler, Bloom, dan WigginsTujuan: Penelitian ini bertujuan merumuskan kerangka konseptual evaluasi holistik dalam desain pembelajaran Pendidikan Islam (PAI) melalui sintesis teori evaluasi Ralph Tyler, Taksonomi Benjamin Bloom, dan backward design Grant Wiggins. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan metode Qualitative Content Analysis (QCA) atau analisis konten kualitatif untuk mengidentifikasi dan menginterpretasikan hubungan antarkonsep dari literatur primer dan sekunder secara sistematis. Hasil: Sintesis integratif menunjukkan bahwa model Tyler, Taksonomi Bloom, dan backward design Wiggins saling melengkapi dalam membangun ekosistem penilaian yang autentik. Integrasi ketiganya menghasilkan model evaluasi holistik tiga lapisa yait keselarasan struktural, instrumentasi multidimensional, dan orientasi autenti yang mencakup dimensi 'ilm (kognitif), akhlaq (afektif), dan amal (psikomotorik) secara terpadu. Kesimpulan: Kerangka konseptual ini memperkuat kualitas desain pembelajaran PAI melalui evaluasi yang selaras, multidimensional, dan berbasis nilai-nilai Islam. Kontribusi: Penelitian ini menawarkan model integratif yang orisinal sebagai acuan operasional bagi pendidik, pengembang kurikulum, dan pembuat kebijakan dalam merancang sistem penilaian PAI yang komprehensif dan kontekstual.